2010
DOI: 10.1088/0953-8984/22/39/393001
|View full text |Cite
|
Sign up to set email alerts
|

Low-dimensional surface oxides in the oxidation of Rh particles

Abstract: The oxidation of rhodium particles leads to the formation of low-dimensional nanostructures, namely ultrathin oxide films and stripes adsorbed on the metallic surface. These structures display unique electronic and structural properties, which have been studied in detail experimentally and theoretically in recent years. In this review, the state of research on low-dimensional surface oxides formed on Rh surfaces will be discussed with a special focus on the contributions derived from computational approaches. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 102 publications
4
8
0
Order By: Relevance
“…In the recent years, density functional theory (DFT) approaches have evolved as powerful tools to complement the experimental efforts to resolve the atomic structure of supported surface oxides [4][5][6], and to analyze the underlying electronic structure and the concomitant magnetic ordering. In this letter, we present extensive DFT calculations for two different CoO c(10×2) overlayer structures supported on Ir(100).…”
mentioning
confidence: 99%
“…In the recent years, density functional theory (DFT) approaches have evolved as powerful tools to complement the experimental efforts to resolve the atomic structure of supported surface oxides [4][5][6], and to analyze the underlying electronic structure and the concomitant magnetic ordering. In this letter, we present extensive DFT calculations for two different CoO c(10×2) overlayer structures supported on Ir(100).…”
mentioning
confidence: 99%
“…The surface density of the nucleation sites of the Rh2O3 clusters can be straightforwardly quantified from the amount of the [RhCl6] 3adsorption sites that were not regenerated by calcination after the first SEA step per unit surface area of CeO2 in the W(1.3)-CeO2 pristine support. This density, estimated to be about 0.05 nucleation site /nm 2 CeO2 (0.065 / 100 / 102.91 x 6.02 x 10 23 / (76 x 10 18 )), appears to be about 3.5 times lower than that of the Rh surface density (0.18 Rh/nm 2 CeO2) after the first SEA step in agreement with the deduced atomicity of the Rh2O3 clusters on Rh/W(1.3)-SEA1.Computational studies concluded to a relatively strong interaction of the RhOx clusters with the CeO2 (111) surface,[78][79][80] in line with HRTEM observations,79 leading to the formation of two-dimensional (2D) clusters/films. The formation of such 2D clusters would be at the origin of their pronounced resistance to sintering under oxidizing conditions79 in agreement with the earlier statements of Van Delft and Nieuwenhuys for oxide layers on reducible supports 81.…”
mentioning
confidence: 60%
“…However, the electronic structure of the oxide film depends on several factors including thickness, changes in the local stoichiometry, defect sites, surrounding environment etc. [42], thus it is difficult to determine it with accuracy. In order to distinguish it from the bulk Rh2O3, the ultrathin rhodium oxide film will be hereafter referred as RhO x with x<2 so as to take into account the previously proposed O-…”
Section: Nap-xps Characterization Of Thermally Oxidized and Reduced Rmentioning
confidence: 99%